2022
DOI: 10.11591/ijphs.v11i1.21105
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of mental health on online distance learning during COVID-19 among Malaysia vocational students

Abstract: The declaration of the movement control order (MCO) in Malaysia has led to the closure of the education sector due to pandemic coronavirus disease 2019 (COVID-19). The teaching and learning (T&L) structure shifted from conventional classroom education to fully online distance learning (ODL). The unprecedented experience of 'home quarantine' has multifaced impacts on students' mental health. The study aimed to obtain the correlation of technical and vocational education and training (TVET) students' dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
2
8
0
1
Order By: Relevance
“…The result of this study involving stress among students found that 36.4% experienced moderate stress symptoms and 20.5% experienced severe stress. These findings are in line with studies that have been conducted by several researchers in Malaysia (Ghafar et al, 2021;Ahmad et al, 2022) and India (Ahmed and Prashantha, 2018;George and Joseph, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The result of this study involving stress among students found that 36.4% experienced moderate stress symptoms and 20.5% experienced severe stress. These findings are in line with studies that have been conducted by several researchers in Malaysia (Ghafar et al, 2021;Ahmad et al, 2022) and India (Ahmed and Prashantha, 2018;George and Joseph, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…As for the findings of a recent study through the assessment of the level of anxiety, it was reported that more than half of the participants experienced very severe anxiety (52.3%), followed by severe anxiety by 27.5%. These findings were consistent with a similar study by Astutik et al (2020), who found that the level of anxiety among newly established remote campus students in Indonesia was 51.1%, and another study from universities in Malaysia in 2021 reported 47% reported mild to very severe anxiety symptoms (Ahmad et al, 2022). Those involved fall under the category of higher COVID-19 disease-related anxiety levels (Cleofas and Rocha, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…suicidal thoughts, post-traumatic stress disorder (PTSD) (Copeland et al, 2021;Fawwaz et al, 2021). The mental health issues among university students going through ODL were increasingly becoming more severe and should not be taken lightly by academicians, family members, and/or the government (Lyubetsky et al, 2021;Ahmad et al, 2022). In addition, the risk factors associated with mental health issues were also found to be due to socio-demographic, economic, social, and health-related factors (Wathelet, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%